Downsizing of rectal cancer following neoadjuvant radiotherapy (5 × 5 Gy) and long interval surgery evaluated using MRI semiautomated volumetric measurements, a retrospective study - Albrecht, Hendrik Christian; Wagner, Sophie; Sandbrink, Christoph; Gretschel, Stephan (Frontiers in Surgery, 2023)
Neoadjuvant conventional chemoradiation (CRT) is the standard treatment for primary locally non-curatively resectable rectal cancer, as tumor downsizing may allow R0 resectability. Short-term neoadjuvant radiotherapy (5x5 Gy) followed by an interval before surgery (SRT- delay) is an alternative for multimorbid patients who cannot tolerate CRT. This study examined the extent of tumor downsizing achieved with the SRT-delay approach in a limited cohort that underwent complete re-staging before surgery. Between March 2018 and July 2021, 26 patients with locally advanced primary adenocarcinoma (>uT3 or/and N+) of the rectum were treated with SRT-delay. 22 patients underwent initial staging and complete re-staging (CT, endoscopy, MRI). Tumor downsizing was assessed by staging and re-staging data and pathologic findings. Semiautomated measurement of tumor volume was performed using mint LesionTM 1.8 software to evaluate tumor regression. The mean tumor diameter determined on sagittal T2 MRI images decreased significantly from 54.7 (29-74) mm at initial staging to 35.8 (0-62) mm at re-staging before surgery (p <0.001) and to 25.5 (7-58) mm at pathologic examination (p <0.001). This corresponds to a mean reduction in tumor diameter of 33.7 (10.6-100) % at re-staging and 51.4 (-4.2-87) % at pathology. Mean tumor volume determined from transverse T2 MR images mint LesionTM 1.8 software significantly decreased from 27.6 (8.7 - 85.7) cm3 at initial staging to 12.5 (3.3 - 30.4) cm3 at re-staging (p <0.001), corresponding to a mean reduction of 53.4 (28.2 - 81.9) %. The frequency of positive circumferential resection margin (CRM) (less than 1mm) decreased from 45,5 % (10 patients) at initial staging to 18,2 % (4 patients) at re-staging. On pathologic examination, the CRM was negative in all cases. However, multivisceral resection for T4 tumors was required in 2 patients (9%). Tumor downstaging was noted in 15 of 22 patients after SRT-delay. In conclusion, the observed extent of downsizing is broadly comparable to the results of CRT, making SRT-delay a serious alternative for patients who cannot tolerate chemotherapy. However, complete response is observed more frequently after CRT.